Chemical analyses of shale gas and conventional natural gas - Demirbas, Ayhan; Cek, Nurettin; Acar, Sukru (Taylor & Francis Inc, 2018)
Shale gas is essentially non-traditional natural gas (NG). Shale gas can be considered an unusual alternative energy source. Shale gas production is a method of obtaining the NG trapped between deep underground rocks. Shale gas production is not economical, except for horizontal drilling and hydraulic fracturing methods. Advanced analysis of shale gaseous samples can be done using gas chromatography, mass spectrometry and other modern testing methods. The Orsat apparatus includes three absorption pipettes containing chemical solutions that absorb gases. Absorbents are a 33% by weight aqueous solution of potassium hydroxide (KOH) for carbon dioxide (CO2), alkali pyrogallol for oxygen (O-2) and ammoniacal cuprous for carbon monoxide (CO) measurement. Oxygen is absorbed in alkaline pyrogallol or in a chromous solution. Shale gas can be analyzed best gas chromatographically. The capillary column can be separated from all the hydrocarbons and their isomers by alumina, which is used as a stationary phase in the gas chromatographic column, because alumina is highly selective for hydrocarbons. Silica is a specific adsorbent that exhibits greater applicability for hydrocarbons. The chemical contents of shale gas are similar to those of the conventional NG. The processing, transfer and storage and distribution of shale gas are assumed to be similar to the conventional NG.
Keywords: chemical analysis; natural gas; sedimentary rock; shale gas; unconventional reservoir